A Comparative Study on the Competence of Ideal Teachers According to Al-Ghazali and Abdullah Nashih Ulwan: Their Relevance and Application in the Modern Education System - Mahmudulhassan; Muhammad Abuzar; Shikdar Mohammad Riazul; Obydur Rahman; Abdulrohim E-sor (Walidem Institute and Publishing (WIP), 2024)
This study aims to conduct a comparative study on the concept of ideal teacher competence according to Al-Ghazali and Abdullah Nashih Ulwan, as well as examine their relevance and application in the modern education system. Teacher competence, which includes aspects of knowledge, skills, and morals, is an important element in shaping the quality of education. Al-Ghazali and Abdullah Nashih Ulwan, as prominent scholars, have made significant contributions in formulating the characteristics of the ideal teacher from the Islamic perspective. This study uses a qualitative method with a descriptive-analytical approach, where data is collected through an in-depth literature study of the works of the two figures. The results of the study show that although there are some similarities in the views of Al-Ghazali and Abdullah Nashih Ulwan related to the competence of ideal teachers, such as the emphasis on noble morals and mastery of science, there are also differences in the context of their application. Al-Ghazali emphasizes more on the role of teachers in building the character of students and the educational community, while Abdullah Nashih Ulwan focuses more on the aspects of mastery of knowledge and teaching methods. The novelty of this study lies in a comparative analysis that reveals the relevance of the views of these two scholars in answering the challenges of modern education, including in the application of technology and curriculum development. The implications of this research are expected to be a reference for policymakers and education practitioners in formulating teacher competency development strategies based on Islamic values, which are by the demands of the times without ignoring religious principles.